Kategorisasi Dalil-Dalil Yang Tidak Disepakati (Adillah Mukhtalaf Fiha) Dalam Kajian Usul Fikih (Sebuah Tinjauan Kritis) - Adib, Muhammad (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2023)
This paper presents a critical review of the categorization of debated arguments (adillah mukhtalaf fiha) in the discourse of Islamic legal theory. With a historical perspective, namely regarding the originator and the context surrounding it, it can be concluded that this categorization was born from a certain historical context that is different from the modern historical context. When confronted with the modern context, namely the reality of contemporary Islamic legal discourse, the categorization of debated arguments undergoes correction and even re-conceptualization. These arguments today have become an important methodological part in the process of ijtihad and the development of Islamic law.